Litteratur og politik - Tygstrup, Frederik; Holm, Isak Winkel (K&K - Kultur og Klasse, 2007)
Literature and Politics Literature is political by representing the world. The production of literature is a contribution to a general cultural poetics where images of reality are constructed and circulated. At the same time, the practice of literature is institutionalized in such a way that the form and function of the images of reality it produces are conceived and used in a distinctive way. In this article, we suggest distinguishing between a general cultural poetics and a specific literary poetics by using Ernst Cassirer’s neo-Kantian concept of »symbolic forms«. We argue that according to this view, the political significance of literary representational practices resides in the way they activate a common cultural repertoire of historical symbolic forms while at the same time deviating from the common ways of treating these forms.